Matrix metalloproteinase gene polymorphisms and oral cancer - Pereira, Andresa C.; Dias do Carmo, Elaine; Dias da Silva, Marco A.; Blumer Rosa, Luiz E. [UNESP] (Medicina Oral, S.L., 2012)
Since oral squamous cell carcinoma (OSCC) is the most prevalent malignant cancer in the oral cavity, several researches have been performed to study the role of important enzymes in this disease. Among them, the matrix metalloproteinases (MMPs) are highlighted, due to the fact that they are proteinases responsible to degrade many extra-cellular matrix components, making possible the invasion of neoplasic cells. Important tools in cancer prognosis have been utilized aiming to correlate high levels of MMPs and OSCC, such as immunohistochemical, zymographic and mRNA detection methods. However, these techniques are usually applied after cancer detection, characterizing a curative but not a preventive medicine. Trying to make interventions before the development of the disease and making possible the identification of people at high risk and, analysis of modifications in MMP genes has been a chance for modern medicine. Recently, polymorphisms in MMP genes have been related to different neoplasias, including OSCC. Despite investigation is beginning, MMP gene polymorphisms seems to have a promising future in oral cancer research and some of the present results have shown that there are MMP polymorphisms related to an increased risk for developing oral cancer. Key words:Oral cancer, polymorphism, matrix metalloproteinase.